Who are we? : reimagining alterity and affinity in anthropology - Chua, Liana; Mathur, Nayanika (Methodology and history in anthropology ;, 2018)
Who do "we" anthropologists think "we" are? And how do forms and notions of collective disciplinary identity shape the way we think, write, and do anthropology? This volume explores how the anthropological "we" has been construed, transformed, and deployed across history and the global anthropological landscape. Drawing together both reflections and ethnographic case studies, it interrogates the critical--yet poorly studied--roles played by myriad anthropological "we" ss in generating and influencing anthropological theory, method, and analysis. In the process, new spaces are opened for reimagining who "we" are - and what "we," and indeed anthropology, could become.